Overcoming the Gender Contradictions in the System of Higher Vocational Training - L. A. Lukinskaya; V. A. Shupina (Obrazovanie i Nauka, 2015)
The paper presents the research results relating to the peculiarities of gender interaction in the higher vocational education, defined as being inconsistent and contradictory. The methodological basis incorporates the studies by the Russian and foreign scientists taking the androgyny as the optimal model of gender interaction. The authors present their model of gender behavior integrating the best traits of feminine and masculine behavior in professional sphere, and based on the analysis of such concepts of gender pedagogy as gender asymmetry, the gender stereotype, the gender display, and their manifestations in educational process.